2022
DOI: 10.3390/antiox11081487
|View full text |Cite
|
Sign up to set email alerts
|

Reverse and Forward Electron Flow-Induced H2O2 Formation Is Decreased in α-Ketoglutarate Dehydrogenase (α-KGDH) Subunit (E2 or E3) Heterozygote Knock Out Animals

Abstract: α-ketoglutarate dehydrogenase complex (KGDHc), or 2-oxoglutarate dehydrogenase complex (OGDHc) is a rate-limiting enzyme in the tricarboxylic acid cycle, that has been identified in neurodegenerative diseases such as in Alzheimer’s disease. The aim of the present study was to establish the role of the KGDHc and its subunits in the bioenergetics and reactive oxygen species (ROS) homeostasis of brain mitochondria. To study the bioenergetic profile of KGDHc, genetically modified mouse strains were used having a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 74 publications
(120 reference statements)
0
13
0
Order By: Relevance
“…Studies that used permeabilized rat skeletal muscle mitochondria, intact and permeabilized mouse liver mitochondria, cultured macrophages, and heart mitochondria has revealed PDHc, KGDHc, BCKDHc, and OADHc display rates of mtO 2 •- /mtH 2 O 2 greater than complex I [ 1 , 49 , 83 , 84 , [86] , [87] , [88] , [89] ]. Horvath et al reported KGDHc is also an important mtO 2 •- /mtH 2 O 2 generator in mouse brain tissue when the ETC is operating under RET conditions [ 90 ]. In this case, mitochondrial fuels like succinate and glycerol-3-phosphate, which by-pass the Krebs cycle and donate electrons directly to coenzyme Q 10 (CoQ) in the ETC, generate mtO 2 •- /mtH 2 O 2 by KGDHc by producing NADH at complex I [ 90 ].…”
Section: Kdhc Are Mto 2 •- /Mth ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that used permeabilized rat skeletal muscle mitochondria, intact and permeabilized mouse liver mitochondria, cultured macrophages, and heart mitochondria has revealed PDHc, KGDHc, BCKDHc, and OADHc display rates of mtO 2 •- /mtH 2 O 2 greater than complex I [ 1 , 49 , 83 , 84 , [86] , [87] , [88] , [89] ]. Horvath et al reported KGDHc is also an important mtO 2 •- /mtH 2 O 2 generator in mouse brain tissue when the ETC is operating under RET conditions [ 90 ]. In this case, mitochondrial fuels like succinate and glycerol-3-phosphate, which by-pass the Krebs cycle and donate electrons directly to coenzyme Q 10 (CoQ) in the ETC, generate mtO 2 •- /mtH 2 O 2 by KGDHc by producing NADH at complex I [ 90 ].…”
Section: Kdhc Are Mto 2 •- /Mth ...mentioning
confidence: 99%
“…Horvath et al reported KGDHc is also an important mtO 2 •- /mtH 2 O 2 generator in mouse brain tissue when the ETC is operating under RET conditions [ 90 ]. In this case, mitochondrial fuels like succinate and glycerol-3-phosphate, which by-pass the Krebs cycle and donate electrons directly to coenzyme Q 10 (CoQ) in the ETC, generate mtO 2 •- /mtH 2 O 2 by KGDHc by producing NADH at complex I [ 90 ]. Together, a significant amount of evidence has been generated demonstrating the KDHc family of enzymes are main mtO 2 •- /mtH 2 O 2 sources in mammalian mitochondria.…”
Section: Kdhc Are Mto 2 •- /Mth ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, complex I and III of the ETC are often viewed as the main sources of mH 2 O 2 , but this convention has been challenged by the growing evidence showing PDH and KGDH are important mH 2 O 2 generators. Several studies demonstrated KGDH has a high mH 2 O 2 production rate in synaptosomes and isolated mitochondria (Horvath et al , 2022; Starkov et al , 2004; Tretter & Adam-Vizi, 2004). It was reported later that KGDH is 8x more effective at mH 2 O 2 generation when compared to complex I in muscle (Quinlan et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was demonstrated here that the redox-sensitive protein DJ-1 is required to protect the retina and retinal pigment epithelium (RPE) from oxidative-stress-induced degeneration [ 16 ]. This Special Issue also gathered studies focused on the identification of new biomarkers for AD preclinical diagnosis [ 17 ], of new treatments based on the administration of hydroxocobalamin (Hb, vitamin B 12 analog) to prevent cytoplasmic aggregation of TDP-43 observed in many neurodegenerative diseases [ 18 ], of a new mechanism linking astrocyte-derived oxidative stress to motor-neuron damage in ALS [ 19 ], and on the role of the alpha–ketoglutarate dehydrogenase complex (KGDHC), a rate-limiting enzyme in the tricarboxylic acid cycle, whose activity is strikingly reduced in AD [ 16 ], in the bioenergetics and reactive oxygen species (ROS) homeostasis of brain mitochondria [ 20 ].…”
mentioning
confidence: 99%